Sejarah Diaspora Suku Bugis-Makassar di Kalimantan Tengah - Suryanti Suryanti; Ihsan Mz; ST Rahmah (Universitas Islam Negeri Alauddin Makassar, 2020)
The presence of the Buginese-Makassarnese in Indonesia is always interesting when examined from various points of view, especially since this tribe has spread to various regions in the country and even abroad. The Buginese-Makassarnese who settled in Central Kalimantan is interesting to study because their existence still shows a strong engagement to the traditions of their origin. For example, the Buginese-Makassarnese who live in Central Kalimantan still maintains some of their ancestral traditions. Second, this community can also establish a harmonious and peaceful relationship with the Dayak people as the original inhabitant of Central Kalimantan, including other migrant communities from Java, Sumatra, and others. This type of research is qualitative with a narrative study approach. Data collection techniques using in-depth interviews and observation. The results of this study reveal that the reason the Buginese-Makassarnese commit diaspora is due to conflict in their hometown and economic motives. For the Buginese-Makassarnese,